The Urgency of Handling Non-Performing Financing in Sharia Banks in the Development of Indonesian Sharia Economics - Renny Supriyatni; Nurjamil Nurjamil (Faculty of Law, Universitas Padjadjaran, 2021)
In Indonesia, non-performing financing in Islamic banking has a significant impact on banking system, soundness level of bank, and national economy. Proper handling can minimize the risks so that Islamic banking can continue to develop. This study elaborated the urgency of handling problematic financing in Islamic banks in the development of the Indonesian Islamic economy. This study is a descriptive analytical study with a normative juridical approach. The data was analyzed juridically and qualitatively. Problematic financing in Islamic banks occurs due to internal and external factors. On the other hands, Islamic economy, including its handling methods, are guided by the Holy Quran and the hadiths of the Prophet Muhammad (Peace be Upon Him). The guidance are understood contextually. One of the ways is through restructuring. Handling problematic financing is a very important thing, not only in terms of the obligation to settle debts and receivables of a legal subject, but also closely related to the sustainability of the business of Islamic banks since it also has an impact on the development of the Islamic economy in Indonesia. Urgensi Penanganan Pembiayaan Bermasalah pada Bank Syariah dalam Pengembangan Ekonomi Syariah di IndonesiaAbstrakPembiayaan bermasalah yang terjadi pada perbankan syariah berdampak cukup signifikan terhadap system perbankan, tingkat kesehatan bank, dan perekonomian nasional. Penanganan yang tepat dapat meminimalisir risiko yang terjadi sehingga perbankan syariah dapat terus berkembang. Penelitian ini dilakukan untuk mengelaborasi urgensi penanganan pembiayaan bermasalah pada bank syariah dalam pengembangan ekonomi syariah di Indonesia. Penelitian ini merupakan penelitian yang bersifat deskriptif analitis dengan metode pendekatan yuridis normatif dimana data dianalisis secara yuridis kualitatif. Pembiayaan bermasalah pada bank syariah terjadi karena factor internal maupun ekternal yang metode penanganannya dituntun di dalam al-Qur’an yang didukung oleh hadits-hadits Nabi yang difahami secara kontekstual dimana cara yang dilakukan adalah melalui restrukturisasi. Penanganan pembiayaan bermasalah merupakan satu hal yang sangat penting, bukan hanya dari sisi kewajiban penyelesaian utang piutang seorang subyek hukum, akan tetapi juga erat kaitannya dengan keberlangsungan usaha bank syariah yang juga berdampak pada pengembangan ekonomi syariah di Indonesia.Kata kunci: bank syariah, ekonomi syariah, pembiayaan bermasalah.DOI: https://doi.org/10.22304/pjih.v8n1.a2